Effect of pre-harvest sprays of growth regulators and chemicals on storage life of garlic (Allium sativum L.) - S Patil, B R Kumara, (Journal of Spices and Aromatic Crops, 2015)
The effect of pre-harvest treatments involving combinations of different chemicals and growth regulators viz., maleic hydrazide (MH), MH + carbendazim, MH + dithane M-45, cycocel (CCC), CCC + carbendazim, CCC + dithane M- 45, borax, borax + carbendazim on storage life of garlic was studied. Among the treatments, minimum physiological loss in weight (30.67%) was recorded with the pre-harvest spray of MH (2500 ppm) + carbendazim (1000 ppm), three weeks prior to harvest followed by MH (2500 ppm) three weeks prior to harvest. Application of CCC (1000) ppm + dithane M- 45 (1000 ppm) showed maximum recovery of healthy cloves (41.04%) at the end of 180 days of storage.